2021
DOI: 10.1039/d1cp00703c
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous TMAO solution under high hydrostatic pressure

Abstract: Trimethylamine N-oxide (TMAO) is a well-known osmolyte in nature, which deep-sea fish use to stabilize proteins against High Hydrostatic Pressure (HHP). We present a combined ab initio molecular dynamics, force...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
4
7
0
Order By: Relevance
“…In our simulations TMAO increases protein stability in the presence of thermal stress, consistent with its behavior in simulations at high pressure (6,14) or in the presence of denaturants (14,16,21,31). Mechanistically, most TMAO resides in an outer methyl-towards-protein shell at ~5.5 Å, but an oxygen-towards-protein inner shell of TMAO molecules interacts directly with basic side chains (~2.5 Å) at the protein surface, cooperating in a push-pull effect to herd water molecules towards the protein even at high temperature.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our simulations TMAO increases protein stability in the presence of thermal stress, consistent with its behavior in simulations at high pressure (6,14) or in the presence of denaturants (14,16,21,31). Mechanistically, most TMAO resides in an outer methyl-towards-protein shell at ~5.5 Å, but an oxygen-towards-protein inner shell of TMAO molecules interacts directly with basic side chains (~2.5 Å) at the protein surface, cooperating in a push-pull effect to herd water molecules towards the protein even at high temperature.…”
Section: Discussionsupporting
confidence: 87%
“…S10). Though earlier studies have supported TMAO accepting 3 hydrogen bonds from water (48)(49)(50), a recent study suggests that TMAO can form up to 4 hydrogen bonds with water at high pressure, and we see this effect on a smaller scale in our variable temperature simulations as well (6). The ability of TMAO to form up to four hydrogen bonds with water may be one of the reasons it is able to disrupt water structure and herd more water molecules towards the protein surface, and why the effect quickly saturates with TMAO concentration.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…X-ray absorption spectroscopy studies by Knierbein et al 50 demonstrated that water is less compressible with increasing TMAO concentration. Fourier transform infrared spectroscopy measurements by Imoto et al 71 and THz spectroscopy measurements by Kolling et al 72 observed a blueshift of the bending/stretching modes associated with the hydrophobic methyl groups on TMAO with increasing pressure, corresponding to increased hydration. However, the modes related to hydrogen bonding to the TMAO NO group were observed to redshift, corresponding with weakened TMAO–water hydrogen bonding with increasing pressure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the modes related to hydrogen bonding to the TMAO NO group were observed to redshift, corresponding with weakened TMAO–water hydrogen bonding with increasing pressure. To gain further atomistic level structural information, these studies are supplemented with ab initio and classical MD to understand the origin of these frequency shifts 71 , 72 . Increased pressure results in a shift from a predominantly three-fold coordinated TMAO oxygen to an increasingly prominent 4-fold coordination.…”
Section: Introductionmentioning
confidence: 99%